Georgia Architectural and Historic Properties Survey of Rural [109] Mid western section of the county, Quitman, Ga. December 1980 - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Rural [109] Mid western section of the county, Quitman, Ga. December 1980. A one story rectangular plan with gabled and hipped tin roof, clapboard siding, central gable. Shed porch, square posts. Sash windows with 6/6 lights. Interior chimney, brick piers. Fair condition. Date of Construction: c. 1910. A typical vernacular farmhouse common in this area.
Georgia Architectural and Historic Properties Survey of Rural [109] Mid western section of the county, Quitman, Ga. December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 1 scan. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 918 KB (940,429 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Brooks County (Ga.); Quitman (Ga.)